Sleep problems in out-patient of primary care unit - Saisunee Tubtimtes (2018)
Objective: The prevalence and factors associated with sleep problems among out-patients of the Family Medicine Department in Ramathibodi Hospital were evaluated and their management was assessed. Material and Method: Descriptive study, out-patients in family medicine clinic (n = 512) were selected by stratified random sampling. Sleep problems during the previous month were assessed by using questionnaires. Excessive daytime sleepiness (EDS) was assessed by Epworth sleepiness scale. The medical records of 45 patients with habitual insomnia during the previous 6 months were retrieved to study its management. The data were analyzed by Chi-square, Odds ratio, 95% Confident Interval and binary logistic regression. Results: Half of the subjects (50.4%) had chronic diseases. Age range was 20-78 years old and 69.9% were female. Insomnia distributed almost equally in all age groups. Approximately 57.9% and 19.5% of the subjects reported insomnia and sleepiness. One fourth of the participants (24.7%) had snored and this was more often in men than women (OR 1.7). Anxiety score, female, and perception of their illness and disease were strong factors associated with insomnia. Most of them (71.1%) did not consult their doctors despite having habitual insomnia. From medical records reviewed, only one fourth of them (28.9% and 26.7%) were recorded about the insomnia and the prescriptions. Conclusion: More than half of the out-patients in primary care had sleep problems, especially insomnia, and excessive daytime sleepiness, but few of them consulted their doctors. This problem should not be overlooked. Psychological problems and anxiety with their illness were associated with insomnia. Therefore, exploring and understanding their problems are important issues to manage and render advice for their quality sleep.